Developing a Culturally Restorative Approach to Aboriginal Child and Youth Development: Transitions to Adulthood - Simard, Estelle; Blight, Shannon (First Peoples Child & Family Review, 2011)
An innovative approach to providing “care” to Aboriginal child who are making a transition into adulthood embodies the concept of culturally restorative practice. This paper is a literature review on Aboriginal child development for children and youth transitioning from a youth to an adult. This paper contains excerpts from “Developing a Culturally Restorative Approach to Aboriginal Child and Youth Development: Transitions to Adulthood” published as a social policy paper for Ontario’s Ministry of Child and Youth Services. The paper was a review of the literature of the following: culturally restorative practices, best practices for successful engagement with Aboriginal populations, thematic of Aboriginal development, as well as implications for child and youth services.